Laparoscopic versus robotic radical hysterectomy after neoadjuvant chemotherapy in locally advanced cervical cancer: A case control study. Issue 1 (January 2015) - Vizza, E.; Corrado, G.; Mancini, E.; Vici, P.; Sergi, D.; Baiocco, E.; Patrizi, L.; Saltari, M.; Pomati, G.; Cutillo, G.
Abstract Objective To compare the surgical outcome of robotic radical hysterectomy (RRH) versus laparoscopic radical hysterectomy (LRH) for the treatment of locally advanced cervical cancer (LACC) after neoadjuvant chemotherapy (NACT). Materials and methods From August 1st 2010 to July 1st 2012 a prospective data collection of women undergoing RRH for cervical cancer stage FIGO IB2 to IIB, after neoadjuvant chemotherapy, was conducted at National Cancer Institute "Regina Elena" of Rome. All patients deemed operable underwent class C1 RRH with pelvic lymphadenectomy within 4 weeks from the last chemotherapy cycle. Results A total of 25 RRH were analyzed, and compared with 25 historic LRH cases. The groups did not differ significantly in body mass index, stage, histology, number of pelvic lymph nodes removed. The median operative time was the same in the two groups with 190 min respectively. The median estimated blood loss (EBL) was statistically significant in favor of RRH group. Median length of stay was shorter, for the RRH group (4 versus 6 days, P = 0.28). There was no significant difference in terms of intraoperative and postoperative complications between groups but in the RRH group we observed a greater number of total complications compared to the control group. Conclusion This study shows that RRH is safe and feasible in LACC after NACT compare to LRH. However, a comparison of oncologic outcomes and cost–benefit analysis is still needed and it has to be carefully evaluated in the future.